Dynamic Modeling and Simulation for Control Systems - Olaru, Adrian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book contains all the articles published in the Special Issue "Dynamic Modeling and Simulation for Control Systems" from the MDPI Mathematics journal. This Special Issue aims to cover important aspects of how to optimize the dynamic behavior of physical systems using special algorithms and artificial intelligence in the modeling, simulation, and optimization of components and systems from important fields such as astronautics, aerospace, avionics, robotics, manufacturing systems, mechanical engineering, power energy, materials technology, and neurorehabilitation. It is our hope that this Special Issue will contribute to the research on techniques for the modeling, simulation, and optimization of control systems in dynamic systems.